2002
DOI: 10.1063/1.1464827
|View full text |Cite
|
Sign up to set email alerts
|

Lattice models of ionic systems

Abstract: A theoretical analysis of Coulomb systems on lattices in general dimensions is presented. The thermodynamics is developed using Debye-Hückel theory with ionpairing and dipole-ion solvation, specific calculations being performed for 3D lattices.As for continuum electrolytes, low-density results for sc, bcc and fcc lattices indicate the existence of gas-liquid phase separation. The predicted critical densities have values comparable to those of continuum ionic systems, while the critical temperatures are 60-70% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(116 citation statements)
references
References 38 publications
7
109
0
Order By: Relevance
“…The second term in the free energy density is the electrostatic contributionf DH = 20 it can be easily shown that…”
Section: A Thermodynamic Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The second term in the free energy density is the electrostatic contributionf DH = 20 it can be easily shown that…”
Section: A Thermodynamic Overviewmentioning
confidence: 99%
“…This process significantly decreases the number of free ions. In charge-symmetric lattice electrolytes in the critical region the number of neutral ion pairs is 2-3 times larger than the number of free ions, 20 and one can expect that for charge-asymmetric ionic systems this ratio should be even larger because of the larger free energy gain for clusters with the increase of the parameter z.…”
Section: A Bjerrum Clusteringmentioning
confidence: 99%
See 3 more Smart Citations